The Еssence of Russia’s Soft Power in CIS Countries - Yengoyan, Ashot (YSU Journal of International Affairs, 2024)
The article reveals the content of such an important instrument of Russian foreign policy as “soft power”. The manifestation of this phenomenon in Russia differs markedly from other states, especially those that have the appropriate potential for its application, as well as many years of experience in this field. The basic principles of Russia’s “soft power” are developed in the fundamental documents of the country’s main foreign policy agency. They particularly emphasize the need to implement these principles in the post-Soviet space in order to keep it in the orbit of Russian politics. The article provides a comparative analysis of the use of Russian “soft power” in Ukraine, Kazakhstan and Armenia. The main problems and omissions in the course of its implementation are identified, as well as the reasons for the low efficiency of the activities of some Russian foreign policy departments.
Keywords: “soft power”; concept of Russian foreign policy; “smart power”; post-Soviet countries; corruption; civilization, policy, economy, Eurasian Union, security, post-Soviet territory, national interests; ideological and value orientations; energy policy